Punishment before trial: public opinion, perp walks, and compensatory justice in the United States - Van Slyke, Shanna R. (Crime, law and social change, 2023)
The presumption of innocence, the prohibition against pretrial punishment, and the right to an impartial jury - constitutional bedrocks of the American criminal justice process - are potentially threatened by the practice of "perp walks." Justice officials, politicians, and the news media have cited public demand as one justification for this controversial practice. Yet, this justification lacks an empirical basis. Drawing from work on procedural fairness, the present study suggests compensatory justice as a framework for understanding why some American citizens might support perp walks. We extend research on public attitudes towards perp walks with data from an internet survey of 1000 U.S. adults. We find that perp walks are not supported by a majority of the public and that attitudes towards perp walks are influenced by perceptions of the pros and cons of perp walks as well as of the legitimacy of the justice system.